“The interconnectedness and spiritual equality of all things”: Recovering indigenous ecological imagination in postcolonial Australian fiction - Brown, JM (Taylor and Francis, 2022)
Following the 1992 Mabo Decision which overturned the historical myth of terra nullius and its declaration that Australia was “nobody’s land,” Indigenous Australian literature has been concerned with recovering both the sidelined historical of colonial dispossession and traditional ecological knowledge. Inspired by their own storytelling traditions, First Nations writers Kim Scott and Alexis Wright reveal these Indigenous histories and cultures through their explorations of “Country”: an Aboriginal English word encompassing the belief that all things, human and non-human, are equally and spiritually connected across time in an ecological web of stories. By examining the interrelationship of postcolonialism and ecocriticism, I argue that Scott and Wright, through their respective novels That Deadman Dance and Carpentaria, promote diverse, Indigenous understandings of the environment, challenging the dominance of Anglo-American writing in ecocriticism. Alongside its capacity to interrogate the way we read and analyze nature and history, I also argue that Indigenous writing has the capacity to challenge the novel form itself by moving away from Western conceptions of linear temporality, casual development, and action or character driven plot, and instead incorporating traditional storytelling modes (oral stories, music, and dance) that are all framed by the rhythmed events of ecological time and place.